Mobilizing human capital in information technology projects: Interactions, negotiations, and actions of distributed actors. - Shrihari Suresh Sohani; Manjari Singh; Biju Varkkey (PLoS ONE)
The study explores the interaction of two cross-functional distributed actors (HR and project managers), their actions, and how they utilize existing practices to mobilize human capital in projects. The study, located at the intersection of practitioners and praxis, explores how the flow of different HR activities is constructed during project execution. Based on extensive field-based qualitative research and anchored on the micro foundations' lens, we find that paired distributed actors (project manager and HR manager) engage in two mutually exclusive strategizing practices (human resource procedurally embedded and human resource interactive and mutual) for shaping the activity flow of HRM implementation. This finding is critical because it explains how the tension between the paired distributed actors is handled during project execution in project-based firms.